THE EFFECT OF GLYCERIN APPLICATION ON ROUGHNESS OF NANOHYBRID COMPOSITE RESIN IMMERSED IN ISOTONIC DRINK - Laila Rahma Milenia; Surya Nelis; Brigitta Natania Brigitta Natania Renata Purnomo; Nadia Hardini (FKG Unlam, 2023)
ABSTRACTBackground: Composite resin is the most commonly used restorative material. One type of composite resin based on the filler material is a nanohybrid composite resin which has the advantage of good strength and smooth surface to produce good improvements in terms of durability and aesthetics. The roughness of the resin can be affected by drinks with low pHs, such as isotonic drink. Glycerin can reduce the roughness of the composite resin by acting as a barrier so that an oxygen inhibition layer (OIL) is not formed. Purpose: This study is to determine the effect of glycerin application on the roughness of nanohybrid composite resin immersed in an isotonic drink. Method: A total of 32 samples of nanohybrid composite resin used in this study were made with a diameter of 5 mm and a thickness of 2 mm. The nanohybrid composite resin samples were divided into group I without glycerin application and group II with glycerin application before the light curing process. Both groups were then immersed in an isotonic drink for 18 hours in an incubator. The research continued with roughness testing using a surface roughness tester. Result: There was a significant difference in the roughness of the nanohybrid composite resin immersed in an isotonic drink with and without glycerin application. This is indicated by the p-value < 0.05 in the unpaired bivariate t-test, which means that there is a significant difference in the two sample groups. Conclusion: The application of glycerin can reduce the roughness of the nanohybrid composite resin immersed in isotonic drink. Keywords: Glycerin application, Nanohybrid composite resin, Roughness.